Peningkatan Kualitas Pembelajaran Dengan Model Probing Prompting Di SMP Mangunharjo Tugumulyo Musi Rawas - Ahmad Taufik; Khadafi Ramadhani; Ahmad Budiyono (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
The reality of the arrangement of Islamic religious education subjects has an important function as well as appreciating strategies regarding educational events at every level in educational attainment. However, the capacity of the reality of the time period in the field of Islamic religious education which is held in public schools still gets serious attention where problems and criticisms occur from various parties. Naturally, overcoming the form of shortcomings and weaknesses will practice Islamic religious education subjects in the school environment, at least through the path of manifestation towards the path of change. Therefore, it requires a policy study or a specific study according to the commitment called the reconstruction of Islamic religious education subjects. This study has a purpose, namely to determine the improvement of the quality of learning with the Probing Prompting model in Islamic religious education subjects for students of SMP Mangunharjo Tugumulyo Musi Rawas. This type of research is CAR participants. The place of this research is students at SMP Mangunharjo Tugumulyo Musi Rawas. The implementation time of this research is in the Odd semester 2020/2021 for Islamic religious education subjects. This study carried out several stages in its research, including: monitoring, results, evaluation and reflection. Data analysis technique in the form of quantitative description. the conclusions of this study show: 1). The learning model with the probing prompting model can improve the quality of learning for Islamic religious education subjects, it can be seen from the level of student activity, and test results. 2). Students like this learning model because it makes them always active in learning.